DLNotes2: análise do uso de ferramenta computacional para compreensão leitora de processos argumentativos - Santos, Karina Pacheco dos (2019)
This study aims to evaluate if the structured and semantic annotations made by postsecondary students with the aid of the computational tool DLNotes2 contribute to the understanding of macro and micro textual structures concerning the organization of the argumentative processes in the opinion article genre. The methodology has interpretative character and the analysis of results will be carried out by the following approaches: quantitative, from the reports in Excel generated by the tools DLNotes2 and Google Forms; and qualitative, carried out through analysis, articulated with the theoretical assumptions about argumentation, and from the annotations and questions on interpretation, carried out by the participants of the research. For the constitution of the corpus, a course about reading and interpretation of opinion article genre was offered to students in the first and third year of undergraduation course. In this course, activities of annotation and interpretation of this genre were applied in an analogue media, with paper, pencil and pen; and digital, using the DLNotes2 tool and Google Forms. In the theoretical assumptions of the research, the first chapter presents general notions about technology and its intrinsic relations with language and culture, based on Cupani (2016; 2004), Veraszto et al. (2008) and Hall (1997). In addition, the concept of metalanguage (AUROUX, 1992; NASCIMENTO, 1990) and notions about annotation (BLUSTEIN; ROWE; GRAFF, 2011; MARSHALL, 1997) are discussed. Then, general concepts on multiliteracies, in particular, digital literacy (ZACHARIAS, 2016; XAVIER, 2011), are described and articulated with the explanation of the computational tool DLNotes2 (MITTMANN et al., 2013). In the second chapter, assumptions about argumentation, based on the new rhetoric (PERELMAN; OLBRECHTS-TYTECA, 2005; FIORIN, 2015), are approached in order to establish the categories of analysis addressed in the reading of the genre of opinion, in order to reconstruct the argumentative choices of the text producer. Then, elements of the micro and macro structure of the opinion article genre are described and related to the notions about argumentation (ANTUNES, 2010; BRONCKART, 2007). Also, in the second chapter, the argumentative categories selected for work with reading of the opinion article genre are specified. In the third chapter, the conception, objectives and strategies that guided the work with reading in this study are described, based on Solé (1998, 1996) and Koch and Elias (2013). In addition, general notions about reading in analogue and digital media, from Chartier (1998) and Soares (2002), are discussed. The results indicate that, in the two reading, analogue and digital media, the annotation was a differential to understand the argumentative processes identifiable in the opinion article. However, in comparison with annotations performed in the analogic environment, the tool DLNotes2 takes advantage on the work with metalanguage in regard to the marking of the microstructure in the classification of argumentative operators. It was also possible to verify that the computational tool is not a more evolved way to perform the annotation practice in comparison to the analogue, since, although they are used for the same purpose, both ways present some specific annotation features and procedures.